Evaluating the effectiveness of peroneus longus tendon as an autograft for primary anterior cruciate ligament reconstruction: a prospective study - Shervegar, Satish; Veeraiah, Deepak B.; M. G., Prabhu Vignesh; Venkataramana, Karthik M.; Dyapur, Ningaraj (International Journal of Research in Orthopaedics, 2025)
Background: The most common significant ligamentous injury to the knee joint is an anterior cruciate ligament (ACL) tear. The ACL reconstruction aims to restore knee stability, allow the patient to return to regular activities, including sports, and delay the onset of osteoarthritis. The choice of graft plays a vital role and the most popular autograft for reconstruction is the hamstring tendon graft. Many Orthopaedic surgeons use peroneus longus tendon autograft, and it is biomechanically comparable to a hamstring tendon autograft. The aim of this study is to assess the functional outcome and donor site morbidity and analyses complications of using peroneus longus autograft in ACL reconstruction. Methods: Study was conducted from October 2023 to March 2024 in Sapthagiri Institute of Medical Sciences and Research Centre, Bangalore, Karnataka. Using Consecutive sampling technique, a total of 30 patients who fulfilled the criteria were included and observed prospectively for a period of 1 year. Functional scores were recorded preoperatively and 1 year after surgery using IKDC and lysholm scores. Donor site morbidities were assessed with AOFAS score and MRC grading- plantarflexion at ankle and eversion at subtalar joint. Results: Ankle functions at donor site are preserved well in almost all patients with excellent AOFAS score and attained excellent functional outcome in lysholm as well as IKDC knee score. Conclusion: Peroneus longus tendon serves as a suitable autograft option for ACL reconstruction, due to the convenience of its harvest, an aesthetically pleasing outcome, and the better postoperative knee scores. Additionally, the excision of the peroneus longus tendon has not resulted in ankle instability, making it viable for use as an autogenous graft in ACL reconstruction procedures.